Pathophysiology of Decompression Sickness: Current Insights and Emerging Models - Miarczyński, Jakub; Górski, Szymon; Okupniarek, Joanna; Bartosik, Michalina; Jętasiewicz, Igor; Oborski, Michał; Oborski, Krzysztof; Barczyńska, Katarzyna (Quality in Sport, 2026)
Introduction: Decompression sickness (DCS), commonly known as “the bends,” is a clinical disorder caused by the formation of gas bubbles within tissues or the bloodstream as a result of inert gas supersaturation during or following a decrease in ambient pressure. It most often occurs in the setting of compressed-gas diving, work in pressurized environments such as caissons, or rapid decompression to high altitude, including situations involving reduced cabin pressure or extravehicular activity (EVA) in space suits. DCS may also develop after relatively modest pressure reductions, such as commercial air travel undertaken shortly after scuba diving. Clinical manifestations vary widely, ranging from musculoskeletal pain, lymphedema, and cutaneous rashes to severe neurological deficits and cardiorespiratory collapse. Initial evaluation should include a detailed history of recent diving or altitude exposure, the timing of symptom onset, and a thorough neurological examination. Immediate management consists of high-flow oxygen administration and appropriate fluid resuscitation, either orally or intravenously. Definitive treatment involves hyperbaric oxygen therapy. Although residual symptoms may persist in severe cases, prompt and appropriate treatment generally leads to a favorable outcome.